Novel and Specific MRI Features Indicate the Clinical Features of Patients With Rare Hepatic Tumor Epithelioid Hemangioendothelioma - Zhang, Wei; Zhang, Hongtao; Zhong, Yanwei; Zhang, Keming; Kong, Huifang; Yu, Linxiang; Chen, Yan; Bai, Yili; Zhu, Zhenyu; Yang, Yongping; Gao, Xudong (Frontiers in Oncology, 2022)
Objective: To investigate the Magnetic Resonance Imaging (MRI) features and clinical significance of hepatic epithelioid hemangioendothelioma (HEHE). Methods: Clinical records and MRI findings were retrospectively evaluated in nine HEHE patients from May 2010 to January 2020. Result: There were 121 lesions in nine patients with a predominantly peripheral distribution. Five lesions (4.13%) in two patients (22.22%) had evidence of capsular retraction, and three patients had lung metastasis (33.33%). Dynamic contrast-enhanced MRI showed progressive enhancement, mainly in two ways: ring enhancement with hypovascularity in four patients (44.44%) and ring enhancement with hypervascularity in five patients (55.56%). Imaging demonstrated a multi-layer ring appearance, which was typically observed on T2-weighted imaging (T2WI). The most common appearance consisted of two layers of varying signal, with some images displaying up to four layers. There were significant differences in the size of lesions between different layers of multi-layer ring appearance (p < .001). All lesions exhibited a two-layer appearance on diffusion-weighted imaging (DWI), with hyperintensity at the periphery and a slightly high signal at the center (except for those with a single layer on T2WI). The ‘vascular penetration sign’ was observed in most lesions, and the blood vessels of 112 lesions (92.56%) were portal vein branches and five (4.13%) were hepatic vein branches. Pulmonary metastasis was found in three patients with the ‘vascular penetration sign’ of hepatic vein branches. Conclusion: The multi-layer ring appearance on T2WI, the ‘vascular penetration sign,’ and the two enhancement patterns may be of great significance in the diagnosis and treatment of HEHE. The ‘vascular penetration sign’ of hepatic vein branches may indicate extrahepatic metastasis.